Attitudes toward digital pill systems for antiretroviral therapy adherence among pregnant and postpartum women living with HIV in South Africa: a qualitative study - Fertig, Madison R.; Lee, Jasper S.; Rabie, Stephan; Tshukuse, Yanga; Ncukana, Mfanelo; Ashar, Devisi A.; Carnes, Chris; O’Cleirigh, Conall; Joska, John A.; Chai, Peter R.; Stanton, Amelia M. (Frontiers in Psychiatry, 2025)
IntroductionIn South Africa (SA), 22.6% of cisgender women aged 15-49 are living with HIV; of these, one in three are pregnant. Perinatal adherence to antiretroviral therapy (ART) is critical to prevent mother to child transmission (MTCT) of HIV. However, there are numerous barriers to adherence (e.g., pregnancy/postpartum physical symptoms, poor mental health, low social support, structural barriers). In the US, digital pill systems (DPS; i.e., ingestible radiofrequency sensors integrated into gelatin capsules that over-encapsulate medications) have been used to measure adherence to preexposure prophylaxis (PrEP) among men who have sex with men. Interventions that incorporate DPS may facilitate ART adherence and reduce risk of MTCT in SA, but preliminary acceptability has not yet been explored in this context.MethodsThirty pregnant (n=15) and postpartum (n=15) women living with HIV who reported ART adherence challenges were introduced to DPS and completed qualitative interviews. Qualitative data were analyzed via rapid qualitative analysis.ResultsParticipants reported that they missed approximately 3.0 (SD=2.1) ART doses in the past 30 days. Most participants found the overall DPS concept and its components to be acceptable, including ingesting a radiofrequency sensor and wearing a digital pill Reader, which collects adherence data from the digital pill and relays it to a smartphone via a linked app, as a lanyard. They suggested that DPS would improve their adherence and increase accountability to prevent HIV transmission to their infants. Participants who disclosed their HIV status to close friends and family viewed wearing the Reader for several minutes a day to be acceptable and appreciated that providers could access adherence data. They also expressed that the smartphone app would provide helpful reminders to collect and take their ART. However, for both pregnant and postpartum participants, the primary barrier to likely use of the DPS for themselves or others was the risk of involuntary HIV status disclosure by wearing the visible Reader.DiscussionFuture research should explore ideal Reader systems to facilitate use among this population in SA, especially among persons who report low ART adherence or have unsuppressed HIV RNA when presenting for antenatal care.